Even the Most Careless Observer: Race, Visual Discernment in Physical Anthropology from Samuel Morton to Kennewick Man - Armstrong-Fumero, Fernando (American Studies, 2018)
This article uses a historical reflection on the physical anthropology of Samuel Morton (1799–1851) to examine the relationship between statistical studies and the visual discernment in academic and popular culture.  Morton’s work involved extensive numerical data sets, but most of his conclusions rested on assessments of facial morphology based on visual discernment and other humanistic methods.  By the end of the nineteenth century, the development of modern statistical methods contributed to new approaches to populations and morphology that undermined the authority of Morton’s visual discernment.  However, the substance of this disciplinary transformation has left a less obvious imprint in popular media that present non-academic publics with “proof” that can be derived from looking at individual faces.  This split between popular and scientific culture, and the apparent continuities between contemporary popular culture and that of Samuel Morton’s day, has important implications for the relationship between science and race in American culture.